Synonymical notes on Apogonia cupreoviridis and A. nigroolivacea (Coleoptera: Scarabaeoidea: Melolonthidae: Diplotaxini) - Bezděk, Aleš (Fundacja Natura optima dux, 2008)
Abstract. Based on study of primary types of some Palaearctic Apogonia Kirby, 1819 species, the following new synonymies are established: Apogonia cupreoviridis Kolbe, 1886 = A. nigroolivacea Heyden, 1886 syn. nov. = A. cupreoviridis miyakona Nomura, 1965 syn. nov. Apogonia cupreoviridis is redescribed and compared with closely related A. bicarinata bicarinata Lewis, 1896. The occurrence of A. cupreoviridis in Japan is confirmed.
Bibliogr. s. 77
S. 71-77 : il. ; 27 cm
Nazwy taksonów w jęz. łac.
Keywords: taxonomy; type designation; new synonymy; Melolonthinae; Scarabaeidae; Diplotaxini; Apogonia